Clinicopathological and dermoscopic features in a case of linear and unilateral basaloid follicular hamartoma - Naziya Muhammed; Atul M Dongre; Uday S Khopkar (Wolters Kluwer Medknow Publications, 2019)
Linear and unilateral basaloid follicular hamartoma (BFH) is a rare disease that manifests with papules and plaques with distribution along lines of Blaschko. It runs a benign course but with the risk of basal cell carcinoma (BCC) in long term course. BCC can be differentiated from BFH with histopathology and immunohistochemistry. Dermoscopic features of BCC are well studied. Dermoscopic features of BFH are not yet described in literature in detail probably due to rarity of the disease. Here, we present a case of extensive linear and unilateral BFH with its clinicohistopathological and dermoscopic features. The lesions were extensive to involve scalp, face, neck, upper, and lower trunk. Dermoscopy revealed features similar to that of BCC including brown-grey globules and dots, in focus dots, brown linear and arciform structures, crown vessels, short fine telangiectasias, spoke wheel like structures without central dark point, white structureless areas with telangiectasias and keratotic plug. Other dermoscopic features of BCC like arborizing vessels, blue-grey ovoid nests, maple leaf-like areas, concentric structures, ulcerations, erosions and white streaks were absent in this case.